1994
DOI: 10.1007/bf01429221
|View full text |Cite
|
Sign up to set email alerts
|

rDNA site number polymorphism and NOR inactivation in natural populations ofAllium schoenoprasum

Abstract: Nucleolar-organiser activity has been studied by silver staining and by in situ hybridization with an rDNA probe in two populations of Allium schoenoprasum. One population is monomorphic with NORs and rDNA sites terminal on the short arm of pair 8 in all individuals. The other populations is monomorphic for pair 8 NORs but is also polymorphic for NORs on the long arm of pair 7. All plants in this population carry ribosomal cistrons on both chromosomes of pair 7 but 0, 1 or 2 of these sites can be active in rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Variation in the expression of 45S rDNA loci was also reported in H. chilensis (Cerbah et al, 1998a). In H. variegata, the polymorphism observed in the size of the rDNA site could have originated by unequal crossing-over or by amplification and transposition of single rDNA copies, as suggested for other plant species (Schubert and Wobus, 1985;Garrido et al, 1994). Cerbah et al (1998a) suggested that the main 45S rDNA site for the South American species is located on chromosome 3.…”
Section: Localization Of 45s and 5s Ribosomal Genesmentioning
confidence: 63%
“…Variation in the expression of 45S rDNA loci was also reported in H. chilensis (Cerbah et al, 1998a). In H. variegata, the polymorphism observed in the size of the rDNA site could have originated by unequal crossing-over or by amplification and transposition of single rDNA copies, as suggested for other plant species (Schubert and Wobus, 1985;Garrido et al, 1994). Cerbah et al (1998a) suggested that the main 45S rDNA site for the South American species is located on chromosome 3.…”
Section: Localization Of 45s and 5s Ribosomal Genesmentioning
confidence: 63%
“…None of the American samples showed such an increase. On the other hand, in other crop species it has been reported that the number of ribosomal sites tends to rather diminish than increase during the evolution (MALUSZYNSKA and HESLOP-HARRISON 1993b;FUKUI et al 1994;GARRIDO et al 1994). It is also worth of notice that no variation for the position and number of the 5S rDNA sites is present (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…The copy number and chromosomal location of rDNA could be rapidly changed in plant genomes (SCHUBERT and WOBUS 1985;RAI-NA and MUKAI 1999), and chromosomal rDNA distribution often varies among closely-related taxa, even if within species (GARRIDO et al 1994). Variation in the amount of rDNA genes has demonstrated to be on the basis of most of these polymorphisms, as revealed by in situ hybridization (WARBURTON and HENDERSON 1979;KING et al 1990;CASTRO et al 1998).…”
Section: Discussionmentioning
confidence: 99%